Responses of four submerged macrophytes to freshwater snail density (Radix swinhoei) under clear‐water conditions: A mesocosm study. Issue 14 (23rd June 2020) - Zhi, Yongwei; Liu, Yang; Li, Wei; Cao, Yu
Abstract: Macrophytes play a key role in stabilizing clear‐water conditions in shallow freshwater ecosystems. Their populations are maintained by a balance between plant grazing and plant growth. As a freshwater snail commonly found in shallow lakes, Radix swinhoei can affect the growth of submerged macrophytes by removing epiphyton from the surface of aquatic plants and by grazing directly on macrophyte organs. Thus, we conducted a long‐term (11‐month) experiment to explore the effects of snail density on macrophytes with distinctive structures in an outdoor clear‐water mesocosm system (with relatively low total nitrogen (TN, 0.66 ± 0.27 mg/L) and total phosphorus (TP, 36 ± 20 μg/L) and a phytoplankton chlorophyll a (Chl a ) range of 14.8 ± 4.9 μg/L) based on two different snail densities (low and high) and four macrophyte species treatments ( Myriophyllum spicatum, Potamogeton wrightii, P. crispus, and P. oxyphyllus ). In the high‐density treatment, snail biomass and abundance (36.5 ± 16.5 g/m 2 and 169 ± 92 ind/m 2, respectively) were approximately twice that observed in the low‐density treatment, resulting in lower total and aboveground biomass and ramet number in the macrophytes. In addition, plant height and plant volume inhabited (PVI) showed species‐specific responses to snail densities, that is, the height of P. oxyphyllus and PVI of M. spicatum were both higher under low‐density treatment. Thus, compared with low‐density treatment, the inhibitory effects of long‐term high snail density on macrophytes by direct feeding may be greater than the positive effects resulting from epiphyton clearance when under clear‐water conditions with low epiphyton biomass. Thus, under clear‐water conditions, the growth and community composition of submerged macrophytes could be potentially modified by the manual addition of invertebrates (i.e., snails) to lakes if the inhibitory effects from predatory fish are minor. Abstract : In the study, we conducted a long‐term (11‐month) experiment to explore the effects of snail density on macrophytes with distinct structures in an outdoor clear‐water mesocosm based on different snail density and macrophyte species treatments. Our results indicated that high snail density reduced total biomass of submerged macrophytes and ramet number. In addition, plant height and plant volume inhabited showed species‐specific responses to snail densities.